Pengaruh Pemberian Hidrogen Peroksida dengan Dosis Berbeda dalam Menekan Vibrio sp. pada Air Media Budidaya Udang Vaname (Litopenaeus vanamei) (Fauna: Jurnal Kajian Ilmu Hewani, 2026)
Vaname shrimp is one of the export commodities with high economic value. Therefore, to meet increasing market demand, it is necessary to improve aquaculture productivity. However, the development of vaname shrimp farming in Indonesia faces several challenges, including the emergence of viral, fungal, and bacterial diseases (Astria et al., 2022). Vibrio sp. bacteria can cause bacterial infections and are opportunistic in nature. Vibrio sp. can attack shrimp at all stages and may lead to decreased production yields (Astria et al., 2022). Generally, farmers control bacterial diseases by adding antimicrobial compounds. However, bacterial disease control in vaname shrimp culture can also be carried out using hydrogen peroxide (Astria et al., 2022). This study examined the effect of different doses of hydrogen peroxide in suppressing Vibrio sp. bacteria using a Completely Randomized Design (CRD). The doses used were 7 ppm, 9 ppm, 11 ppm, 13 ppm, and 15 ppm, with five treatments and five replications. The results showed that the application of different doses of hydrogen peroxide had a significant effect based on the One Way ANOVA test (0.00 < 0.05). The lowest effectiveness was observed in treatment 1 (7 ppm), while the highest effectiveness was found in treatment 5 (15 ppm). Although hydrogen peroxide was able to reduce the number of Vibrio sp. bacterial colonies, the doses used in this study were not able to completely eliminate the colonies (0 cfu/ml).